Relationship between plasma lipid profile and the severity of diabetic retinopathy in type 2 diabetes patients (Medical Journal of Indonesia, 2008)
This study aimed to determine the relationship between plasma lipid profile and the severity of diabetic retinopathy in type 2 diabetes patients. A cross sectional study was done in Ophthalmologic Clinic, Cipto Mangunkusumo General Hospital, Jakarta for 52 diabetic retinopathy (DR) patients. Data collected were demographic, life style, duration of diabetes, physical and antropometric examinations, fat, fatty acid and cholesterol intake, fasting plasma glucose, A1C, total-, LDL-,HDL-cholesterol and triglyceride level, and fundus examination. Statistical analysis was done using chi-square test to see the associations between plasma lipid profile and DR in type 2 diabetes patients. Subjects comprised of 20 males and 32 females diabetes patients with mean age of 53.8 ± 5.2 years. As much as 53.8% had been diagnosed as DM for >10 years. The mean value of BMI was 24.1 ± 3.3 kg/m2 and 38.5% were classified as obese I and II. The mean value of fasting plasma glucose was 157.5 ± 71.8 mg/dL, and A1C was 9.1 ± 2.4 %. For lipid profile, 40.4% had high total cholesterol level (>240 mg/dL), 34.6% had high and very high LDL-cholesterol level (≥160 mg/dL), and 65.4% had normal HDL-cholesterol (40-60 mg/dL) and triglyceride level (<150 mg/dL). For the severity of retinopathy, 61.6% had severe non-proliferative diabetic retinopahy (NPDR) and proliferative diabetic retinopahy (PDR). In conclusion, there were no significant associations between plasma lipid profile and the severity of diabetic retinopathy. (Med J Indones 2008; 17: 221-5)